O briefing e suas relações no processo de projeto de arquitetura - Tajes, Brianne Bopp (2024)
The briefing is a document that determines the scope of a project and is a tool for architects and urban planners to use at the beginning of an architectural design. Based on it, professionals, together with users, establish all the necessary and relevant information to be met. Due to the large amount of information and different resources for application, in some cases, difficulties and failures may occur at this point. In this context, this research studied the briefing within the architectural design process, with an emphasis on the residential context. The objective was to understand the particularities and subjectivities that influence its development and constitution, identifying how the use of images, protagonists of modernity, can enhance or weaken this process of understanding. To this end, the work dialogues with authors such as Durand (1996, 1997 and 2002), and Phillips (2008), in the area of Design. Regarding the methodological scope, a bibliographic review of the topic was carried out in order to promote updates and reflections, in addition to a focal investigation into the regulations that guide the profession, such as: i) NBR 16636-2: 2017; ii) Brazilian Association of Architecture Offices (AsBEA); iii) and, as an international parameter, the Royal Institute of British Architects (RIBA, 2020), with the purpose of clarifying the technical aspects of this stage. After verifying the aforementioned documents, a semistructured interview and a virtual questionnaire were applied, carried out with professionals who work in the residential market, for the practical understanding of the briefing. The study indicated that Brazilian regulations are broad in their guidelines, however the international regulation analyzed is specific in providing guidance to professionals. Therefore, the Brazilian context provides greater autonomy for the development of the briefing. Therefore, this document can be understood as a creation of the architect, however, when the client plays the role of co-author, he can contribute to the process and obtain enriching results. Therefore, the reflections produced within the scope of this research proved to be relevant because they can support and guide the conception and application of the briefing in a safe manner, as well as in the planning and use of images, contributing to the qualification of the exercise of the profession.